A spy by nature [compact disc, unabridged] - Cumming, Charles, 1971- (Tantor Audio, 2007)
"Alec Milius is young, smart, and ambitious. He also has a talent for deception. He is working in a dead-end job when a chance encounter leads him to MI6, the elite British Secret Intelligence Service, handing him an opportunity to play center stage in a dangerous game of espionage." "In his new line of work, Alec finds that the difference between the truth and a lie can mean the difference between life and death - and he has trouble telling them apart. Isolated and exposed, he must play a role in which the slightest glance or casual remark can seem heavy with unintended menace. Caught between British and American intelligence, Alec finds himself threatened and alone, unable to confide in even his closest friend. His life as a spy begins to exact a terrible price, both on himself and on those around him"--Container.